Applying Sodium Carbonate Extraction Mass Spectrometry to Investigate Defects in the Mitochondrial Respiratory Chain - Robinson, David R. L.; Hock, Daniella H.; Muellner-Wong, Linden; Kugapreethan, Roopasingam; Reljic, Boris; Surgenor, Elliot E.; Rodrigues, Carlos H. M.; Caruana, Nikeisha J.; Stroud, David A. (Frontiers in Cell and Developmental Biology, 2022)
Mitochondria are complex organelles containing 13 proteins encoded by mitochondrial DNA and over 1000 proteins encoded on nuclear DNA. Many mitochondrial proteins are associated with the inner or outer mitochondrial membranes, either peripherally or as integral membrane proteins, while others reside in either of the two soluble mitochondrial compartments, the mitochondrial matrix and the intermembrane space. The biogenesis of the five complexes of the oxidative phosphorylation system are exemplars of this complexity. These large multi-subunit complexes are comprised of more than 80 proteins with both membrane integral and peripheral associations and require soluble, membrane integral and peripherally associated assembly factor proteins for their biogenesis. Mutations causing human mitochondrial disease can lead to defective complex assembly due to the loss or altered function of the affected protein and subsequent destabilization of its interactors. Here we couple sodium carbonate extraction with quantitative mass spectrometry (SCE-MS) to track changes in the membrane association of the mitochondrial proteome across multiple human knockout cell lines. In addition to identifying the membrane association status of over 840 human mitochondrial proteins, we show how SCE-MS can be used to understand the impacts of defective complex assembly on protein solubility, giving insights into how specific subunits and sub-complexes become destabilized.